Hemodialysis Tunneled Catheter-Related Infections. Issue 1 (26th September 2016) - Miller, Lisa M.; Clark, Edward; Dipchand, Christine; Hiremath, Swapnil; Kappel, Joanne; Kiaii, Mercedeh; Lok, Charmaine; Luscombe, Rick; Moist, Louise; Oliver, Matthew; MacRae, Jennifer
Catheter-related bloodstream infections, exit-site infections, and tunnel infections are common complications related to hemodialysis central venous catheter use. The various definitions of catheter-related infections are reviewed, and various preventive strategies are discussed. Treatment options, for both empiric and definitive infections, including antibiotic locks and systemic antibiotics, are reviewed.